Another gazes on the industrial landscape. The island of Zorrozaurre - Cid Blasco, Gracia (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
Since its birth in the 19th century, photography has contributed to making visible the problems that arose in cities during the Industrial Revolution. The city is an ecosystem in a continuous process of transformation and photography, in addition to maintaining its footprint, can help to inspire its future in order to preserve its identity. This article explores this dual role of photography by proposing an approach to the transformation of the industrial landscape based on discovery, the experience of living the place and the use of photography as the main recording device. Based on the theoretical and documentary contribution of the work of some of the main urban photographers, it aims to reveal the keys to a deeper reading of the urban fact; complementary reading to that used in urban planning, inspiring change and aimed at preserving the soul of the city in its historical development. The practical development of a personal photographic essay on the industrial landscape in transition of the Island of Zorrozaurre in Bilbao shows the role of the gaze as a call to action. A new light in which photography plays a fundamental role, not only for its contribution to the field of the tangible but also for its capacity to reveal the intangible aspects of space, those that connect us with its past and meaning.